Titanium-based enamel coating resistant to thermal shock and suitable for low-temperature firing and preparation method thereof

By optimizing the enamel fuse formula and grinding materials, reducing the firing temperature and enhancing the hot and cold impact performance, the problem of insufficient oxidation and hot and cold impact performance of the titanium-based enamel coating under high temperature environment is solved, and the high durability and environmental benefits of the titanium-based enamel coating prepared under low temperature conditions are achieved.

CN119569341BActive Publication Date: 2025-04-25DONGHUA UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510143450.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-02-10
Publication Date
2025-04-25
Estimated Expiration
2045-02-10

AI Technical Summary

Technical Problem

The existing titanium-based enamel coating is easily oxidized under high temperature environments, and it is easy to cause microcracks and expand due to thermal stress during hot and cold impact, resulting in local peeling and affecting the safe operation of the components.

Method used

By optimizing the enamel frit formula, Na2O-B2O3-SiO2 is introduced as the basic system, and a variety of alkaline earth metal oxides such as lithium oxide, BaO, and CaO are added, combined with grinding and adding titanium powder and aluminum silicate fibers, the firing temperature is significantly reduced and the hot and cold impact performance of the coating is enhanced.

Benefits of technology

The titanium-based enamel coating prepared under low-temperature firing conditions is realized, which can be water-cooled at 700°C without cracks and peeling for 22 to 26 times, significantly improving the coating's cold and cold impact resistance and reducing energy consumption and carbon emissions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119569341B_ABST
    Figure CN119569341B_ABST
Patent Text Reader

Abstract

The present invention relates to a titanium-based enamel coating resistant to cold and heat shock and suitable for low-temperature firing and a preparation method thereof, wherein the titanium-based enamel coating comprises an enamel frit and an additive, wherein the additive comprises titanium powder, aluminum silicate fiber, sodium nitrite, clay and water; the preparation method comprises: first preparing an enamel frit, then mixing the enamel frit with the additive to obtain an enamel glaze slurry, then pretreating the titanium substrate to remove surface dirt, then wet-spraying the enamel glaze slurry on the surface of the pretreated titanium substrate, and finally drying and firing the titanium substrate sprayed with the enamel glaze slurry in sequence to obtain the titanium-based enamel coating. The titanium-based enamel coating resistant to cold and heat shock and suitable for low-temperature firing of the present invention can withstand 700°C water cooling cycles for 22 to 26 times without porcelain collapse or shedding, and has excellent cold and heat shock resistance; the preparation process is simple, and the firing temperature is 835 to 845°C, which is more than 60°C lower than the prior art.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of enamel material preparation, and relates to a titanium-based enamel coating which is resistant to cold and heat shocks and suitable for low-temperature firing, and a preparation method thereof. Background Art

[0002] Titanium alloys are widely used in many manufacturing fields due to their excellent specific strength and outstanding corrosion resistance, especially in mechanical equipment that pursues lightweight design, such as aircraft engine blades, fasteners and aircraft structural components. However, in high temperature environments, the surface of titanium alloys is easily oxidized to form a brittle oxygen-rich layer, which limits its direct application in high temperature environments. In order to solve this problem, it is usually necessary to apply a protective coating with excellent high temperature resistance on the surface of titanium alloy parts.

[0003] Enamel coating has become one of the ideal protective materials due to its excellent chemical stability, heat resistance and corrosion resistance. By adjusting the oxide components of the enamel frit, a strong and tight bond can be formed with most metal substrates during high-temperature sintering. However, in practical applications, titanium-based enamel coatings not only need to withstand high temperatures, but also need to cope with the challenges of cyclic thermal shock during heating and cooling. Factors affecting thermal shock performance include the thickness of the enamel coating, the structural design of high-temperature components, the difference in thermal expansion coefficients between the enamel and the titanium substrate, and the generation of interface products. Due to the low toughness of the enamel material itself, microcracks are easily generated due to thermal stress during thermal cycling, and may further expand to cause local peeling, which poses a potential threat to the safe operation of the components.

[0004] To overcome these problems, existing research has adopted a variety of strategies, such as reducing the difference in thermal expansion coefficient between the coating and the substrate, melting rare earth oxides into the enamel frit, and grinding toughening particles into the enamel frit to improve the heat resistance and thermal shock resistance of the enamel.

[0005] Specifically, patent CN101215710A adjusts the expansion coefficient of the coating so that the difference between it and the titanium substrate is less than 5%. The coating is fired at 900-1100°C, with a thickness of 50-180μm, and can withstand 550°C water cooling for 50 times without cracking. However, the firing temperature of the patent is higher than the allotropic transformation temperature of titanium, 882.5°C, and cannot eliminate the thermal stress accumulated by the substrate crystal transformation during the sintering process.

[0006] Patent CN104193173A enhances the high temperature oxidation resistance of titanium-based coatings by grinding rare earth oxides (such as yttrium oxide and cerium oxide), so that the coating can withstand a temperature change of 360~420℃. However, the melting point of rare earth oxides is above 2400℃. Although grinding rare earth oxides can improve the high temperature resistance of enamel, it also increases the firing temperature of enamel. In fact, the firing conditions of the enamel are 900~1000℃ for 1 hour.

[0007] Patent CN107601882A improves the toughness of enamel by grinding and adding aluminum borate whiskers, and the prepared titanium-based coating can withstand a temperature change of 620~680℃. However, the thermal shock performance of enamel is mainly improved by grinding and adding aluminum borate whiskers, and the oxide component of the base enamel frit is not changed. Therefore, the enamel coating still maintains a high firing temperature of 900~930℃.

[0008] In summary, the firing temperature range of titanium-based enamel in the prior art is generally between 900 and 1100°C, while the allotropic transformation temperature of titanium is 882.5°C. When the firing temperature exceeds this critical point, titanium will undergo a crystal transformation from α phase to β phase, accompanied by volume expansion, thereby exacerbating the difference in thermal expansion coefficient between the coating and the titanium substrate, leading to further accumulation of thermal stress and weakening the thermal shock resistance of the coating.

[0009] Therefore, it is of great significance to study a titanium-based enamel coating suitable for low-temperature sintering and having excellent thermal shock resistance and its preparation method in order to improve the reliability and durability of titanium alloy parts under extreme conditions. Summary of the invention

[0010] The purpose of the present invention is to solve the problems existing in the prior art and to provide a titanium-based enamel coating which is resistant to thermal shock and suitable for low-temperature firing and a preparation method thereof.

[0011] To achieve the above object, the technical solution adopted by the present invention is as follows:

[0012] A titanium-based enamel coating resistant to thermal shock and suitable for low-temperature firing, comprising an enamel frit and an additive, wherein the additive comprises titanium powder, aluminum silicate fiber, sodium nitrite, clay and water;

[0013] The formula of the enamel frit is as follows, by mass percentage: SiO2 and B2O3 69-70%, Na2O and Li2O 12-14.5%, two of CaO, BaO and SrO 1-4%, ZnO 1-5%, ZrO2 2-6.5%, TiO2 0-3%, and the balance of two or more of CoO, NiO, CuO, MnO2, MoO3 and Sb2O3;

[0014] Based on the amount of enamel frit, the mass percentages of the components in the grinding additives are: titanium powder 0.25-2%, aluminum silicate fiber 2-3%, sodium nitrite 0.13-0.17%, clay 5-7%, water 33-36%;

[0015] The low temperature sintering temperature is 835~845℃.

[0016] As the preferred technical solution:

[0017] The titanium-based enamel coating resistant to thermal shock and suitable for low-temperature firing as described above has a thickness of 85-115 μm.

[0018] As described above, the titanium-based enamel coating that is resistant to cold and heat shocks and suitable for low-temperature firing is heated to 700°C and kept warm for 20 minutes, then placed in 20°C cold water for cold and heat shocks, and undergoes 22 to 26 cycles of cold and heat shock tests without visible cracks or peeling.

[0019] The present invention also provides a method for preparing a titanium-based enamel coating that is resistant to thermal shock and suitable for low-temperature firing as described above, first preparing an enamel frit, then mixing the enamel frit with an abrasive to obtain an enamel slurry, then pretreating the titanium substrate to remove dirt on the surface of the titanium substrate, then wet-spraying the enamel slurry on the surface of the pretreated titanium substrate, and finally drying and sintering the titanium substrate sprayed with the enamel slurry at 835-845°C in turn to obtain a titanium-based enamel coating that is resistant to thermal shock and suitable for low-temperature firing.

[0020] As the preferred technical solution:

[0021] The preparation method of the titanium-based enamel coating that is resistant to thermal shock and suitable for low-temperature firing as described above, the specific preparation steps are as follows:

[0022] (1) Prepare the batch materials of enamel frit according to the formula:

[0023] (2) placing the batch materials of the enamel frit in a crucible, melting them in an electric furnace with a silicon-molybdenum rod to obtain an enamel melt, drawing the enamel melt with a metal rod, and after testing that there are no nodules within 1 m of the drawn wire, pouring the enamel melt into water for water quenching, and drying to obtain an enamel frit;

[0024] (3) After mixing the enamel frit and the grinding additive, the enamel slurry is obtained by ball milling and sieving;

[0025] (4) Pretreatment of the titanium substrate: polishing the surface of the titanium substrate, then ultrasonically cleaning the titanium substrate with anhydrous ethanol and deionized water respectively, and then drying the titanium substrate with compressed air after cleaning;

[0026] (5) The enamel slurry is wet-sprayed on the surface of the pretreated titanium substrate, and then the titanium substrate sprayed with the enamel slurry is placed in an oven to be completely dried, and then fired in a box-type resistance furnace to obtain a titanium-based enamel coating that is resistant to cold and heat shock and suitable for low-temperature firing.

[0027] In the method for preparing a titanium-based enamel coating that is resistant to thermal shock and suitable for low-temperature sintering as described above, the batch materials of the enamel frit in step (2) are melted at 1540-1570° C. for 100-120 min to obtain an enamel melt.

[0028] In the method for preparing a titanium-based enamel coating that is resistant to thermal shock and suitable for low-temperature firing as described above, the mesh size of the sieve used for screening in step (3) is 60 meshes.

[0029] In the method for preparing a titanium-based enamel coating that is resistant to thermal shock and suitable for low-temperature sintering as described above, in step (4), the surface of the titanium substrate is polished using sandpaper with a mesh size of 40 to 60.

[0030] In the method for preparing a titanium-based enamel coating that is resistant to thermal shock and suitable for low-temperature sintering as described above, the drying temperature in step (5) is 95-105° C. and the drying time is 25-35 min.

[0031] In the method for preparing a titanium-based enamel coating that is resistant to thermal shock and suitable for low-temperature firing as described above, the firing time in step (5) is 9 to 11 minutes.

[0032] Principle of the invention:

[0033] The present invention aims to provide a titanium-based enamel coating with excellent thermal shock resistance and suitable for low-temperature firing and a preparation method thereof. To achieve this goal, the present invention optimizes the oxide components and carefully designs an improved enamel frit formula. On the premise of ensuring a good match between the enamel and the titanium substrate, the firing temperature is significantly reduced, which can be reduced by more than 60°C compared with the prior art; and the thermal shock resistance of the coating is significantly enhanced by grinding and adding a metal toughening phase and a fiber reinforcement phase. Specifically:

[0034] Using Na2O-B2O3-SiO2 as the basic system, a small amount of lithium oxide (Li2O) is introduced by utilizing the mixed alkali effect. Since its lithium ion radius is the smallest, it occupies the network gap after the silicon-oxygen network breaks, making the structure more compact. This not only helps to reduce the firing temperature, but also does not cause volume expansion, thereby maintaining the chemical stability of the enamel. By adding a variety of alkaline earth metal oxides (such as BaO, CaO, etc.), these substances have an aggregation effect on the broken silicon-oxygen network, which can reduce the increase in the expansion coefficient and improve the high-temperature strength and high-temperature stability of the enamel coating.

[0035] Furthermore, the introduction of transition metal oxides such as CoO and Sb2O3 can inhibit the x Si y The generation of interface products enhances the bonding strength between the enamel and the titanium substrate, and by improving the interface properties, ensures the reliability and durability of the coating at high temperatures.

[0036] In order to improve the thermal shock resistance of the coating, the present invention further grinds titanium powder and aluminum silicate fiber on the basis of the above-mentioned enamel frit.

[0037] First, due to its excellent high temperature resistance, aluminum silicate fiber can maintain its structural integrity during the enamel sintering process and form an interlaced network with the enamel matrix. When the enamel layer is subjected to a sudden change in temperature, aluminum silicate fiber can act as a stress dispersion point to cause the cracks to deflect, bifurcate or stop, thereby preventing the expansion of the main crack. Due to its good toughness and plastic deformation ability, metal titanium powder can absorb additional energy during hot and cold shocks and reduce the damage caused by thermal stress to the coating. At the same time, titanium powder can also participate in chemical reactions to generate oxides to fill in possible tiny cracks, preventing them from further developing into larger cracks, and playing a certain self-repairing role.

[0038] Secondly, aluminum silicate fibers, with their unique fiber morphology, form an intricate network structure in the enamel coating. These fibers not only enhance the mechanical properties of the coating, but also act as a physical barrier, effectively reducing the direct contact area between the enamel matrix and the titanium powder particles, reducing the risk of a violent interface reaction between the two, thereby improving the interface bonding strength inside the coating. The low interface bonding strength inside the coating is also one of the reasons for thermal shock failure.

[0039] Thirdly, the thermal conductivity of titanium powder is close to that of titanium substrate. During the thermal shock process, heat can be transferred more evenly between the two, thereby reducing the temperature gradient between the enamel layer and the titanium substrate and the resulting thermal stress. This helps to reduce the risk of damage caused by thermal shock. Both titanium powder and aluminum silicate fiber have relatively low thermal expansion coefficients, which enables them to help adjust the overall thermal expansion behavior of the enamel layer, bringing it closer to the titanium substrate and reducing stress concentration caused by thermal cycling (if the expansion coefficients of the coating and substrate are very different, during heating or cooling, they expand or contract at different rates, which will form stress concentration at the interface). The difference in thermal conductivity between the coating and the substrate is small, and the temperature difference and accumulated thermal stress between the two are small, all of which help to improve thermal shock performance.

[0040] Finally, large bubbles in the enamel coating will reduce the strength of the enamel and cause uneven expansion coefficient and thermal stress inside the enamel during thermal shock. The aluminum silicate fiber provides nucleation points for the bubbles in the enamel coating, which is conducive to the formation of more uniform small bubbles. Due to the steric hindrance effect of the aluminum silicate fiber, it hinders the merging of small bubbles, further inhibits the formation of large bubbles, and maintains a good bubble structure inside the enamel, thereby storing and relieving stress to a certain extent, preventing large-sized bubbles from causing a decrease in the mechanical strength of the coating and uneven expansion coefficient and thermal stress inside the coating.

[0041] Beneficial effects:

[0042] (1) The present invention provides a method for preparing a titanium-based enamel coating that is resistant to cold and heat shock and suitable for low-temperature firing. The firing temperature is 835-845°C, which is more than 60°C lower than that of the prior art, significantly reducing the firing temperature. This innovation effectively avoids the thermal stress generated by high temperature and allotropic transformation of titanium alloy during high-temperature firing, and prevents the interface weakening between the coating and the substrate and the degradation of the mechanical properties of the substrate caused by high temperature. In addition, the low firing temperature reduces energy consumption and carbon emissions, which meets the current global requirements for energy conservation, emission reduction and environmental protection.

[0043] (2) The present invention provides a method for preparing a titanium-based enamel coating that is resistant to cold and hot shocks and suitable for low-temperature sintering. The preparation process is simple and easy to achieve large-scale production and application. The new process is suitable for titanium alloy parts under cold and hot service conditions, and provides a new solution for titanium alloys in aerospace, automobile manufacturing, industrial reactors and other high-temperature application fields. At the same time, the energy savings and environmental benefits brought about by the low sintering temperature also make the technology more attractive and sustainable.

[0044] (3) The titanium-based enamel coating of the present invention, which is resistant to thermal shock and suitable for low-temperature firing, is firmly bonded to the titanium substrate and can withstand 700°C water cooling cycles for 22 to 26 times without ceramic collapse or shedding, and has excellent thermal shock resistance. This performance ensures the stability and reliability of the coating in an extreme temperature change environment, effectively protects the titanium substrate, and extends its service life. This is particularly important for components that need to work in frequent temperature changes. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 This is a macroscopic morphology of the titanium-based enamel coating that is resistant to thermal shock and suitable for low-temperature sintering prepared in Example 1 after 22 cycles of thermal shock tests. DETAILED DESCRIPTION

[0046] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0047] Example 1

[0048] A method for preparing a titanium-based enamel coating that is resistant to thermal shock and suitable for low-temperature firing, the specific steps are as follows:

[0049] (1) In terms of mass percentage, the batch materials for preparing enamel frit are as follows: SiO2 55%, B2O3 14%, Na2O 11%, Li2O 3.5%, CaO 3%, BaO 1%, ZnO 1%, ZrO2 6.5%, TiO2 3%, CoO 1%, and MnO2 1%:

[0050] (2) Melting the batch materials of the enamel frit at 1550°C for 120 min to obtain an enamel melt, drawing the enamel melt with a metal rod, and after testing that there are no nodules within 1 m, pouring the enamel melt into water for water quenching, and drying at 150°C to obtain an enamel frit;

[0051] (3) After mixing the enamel frit and the grinding additive, the mixture is ball-milled and sieved through a 60-mesh sieve to obtain an enamel glaze slurry;

[0052] The grinding additives are titanium powder, aluminum silicate fiber, sodium nitrite, clay and water. Based on the amount of enamel frit, the mass percentages of the components in the grinding additives are: titanium powder 0.25%, aluminum silicate fiber 2%, sodium nitrite 0.15%, clay 6%, water 35%.

[0053] (4) Pretreatment of the titanium substrate: grinding the surface of the titanium substrate with 40-mesh sandpaper, then ultrasonically cleaning the titanium substrate with anhydrous ethanol and deionized water for 30 min respectively, and then drying the titanium substrate;

[0054] (5) Wet-spraying the enamel slurry on the pretreated titanium substrate surface, and then placing the titanium substrate sprayed with the enamel slurry in an oven at 100°C for 30 minutes to dry, and then sintering in a box-type resistance furnace at 840°C for 10 minutes to obtain a titanium-based enamel coating that is resistant to cold and heat shock and suitable for low-temperature sintering;

[0055] Among them, the spraying pressure is 2 atmospheres.

[0056] The thickness of the titanium-based enamel coating that is finally resistant to thermal shock and suitable for low-temperature firing is 110 μm; Figure 1As shown in the figure, the titanium-based enamel coating, which is resistant to thermal shock and suitable for low-temperature firing, is heated to 700°C and kept warm for 20 minutes, then placed in 20°C cold water for thermal shock. After 22 cycles of thermal shock tests, no cracks or peeling visible to the naked eye occur.

[0057] Example 2

[0058] A method for preparing a titanium-based enamel coating that is resistant to thermal shock and suitable for low-temperature firing, the specific steps are as follows:

[0059] (1) In terms of mass percentage, the batch materials for preparing enamel frit are as follows: SiO2 55%, B2O3 14%, Na2O 11%, Li2O 3.5%, CaO 3%, BaO 1%, ZnO 1%, ZrO2 6.5%, TiO2 3%, CoO 1%, and MnO2 1%:

[0060] (2) Melting the batch materials of the enamel frit at 1550°C for 120 min to obtain an enamel melt, drawing the enamel melt with a metal rod, and after testing that there are no nodules within 1 m, pouring the enamel melt into water for water quenching, and drying at 150°C to obtain an enamel frit;

[0061] (3) After mixing the enamel frit and the grinding additive, the mixture is ball-milled and sieved through a 60-mesh sieve to obtain an enamel glaze slurry;

[0062] The grinding additives are titanium powder, aluminum silicate fiber, sodium nitrite, clay and water; based on the amount of enamel frit, the mass percentages of the components in the grinding additives are: titanium powder 2%, aluminum silicate fiber 2%, sodium nitrite 0.15%, clay 6%, water 35%;

[0063] (4) Pretreatment of the titanium substrate: grinding the surface of the titanium substrate with 40-mesh sandpaper, then ultrasonically cleaning the titanium substrate with anhydrous ethanol and deionized water for 30 min respectively, and then drying the titanium substrate;

[0064] (5) Wet-spraying the enamel slurry on the pretreated titanium substrate surface, and then placing the titanium substrate sprayed with the enamel slurry in an oven at 100°C for 30 minutes to dry, and then sintering in a box-type resistance furnace at 840°C for 10 minutes to obtain a titanium-based enamel coating that is resistant to cold and heat shock and suitable for low-temperature sintering;

[0065] Among them, the spraying pressure is 2 atmospheres.

[0066] The final titanium-based enamel coating that is resistant to cold and heat shocks and suitable for low-temperature firing has a thickness of 115μm; the titanium-based enamel coating that is resistant to cold and heat shocks and suitable for low-temperature firing is heated to 700℃ and kept warm for 20 minutes, and then placed in 20℃ cold water for cold and heat shock. After 22 cycles of cold and heat shock tests, no cracks or peeling visible to the naked eye appeared.

[0067] Comparative Example 1

[0068] A method for preparing a titanium-based enamel coating is basically the same as that of Example 2, except that titanium powder and aluminum silicate fiber are omitted from the grinding additives in step (3).

[0069] The titanium-based enamel coating was heated to 700°C and kept warm for 20 minutes, then placed in cold water at 20°C for hot and cold shock. After seven cycles of hot and cold shock tests, cracks appeared on the surface, and local peeling occurred as point-like peeling.

[0070] By comparing Comparative Example 1 with Example 2, it can be found that the thermal shock resistance of the titanium-based enamel coating prepared in Comparative Example 1 is significantly deteriorated. This is because the enamel material is inherently brittle. Once a crack appears, its expansion is difficult to be effectively suppressed, and the crack is not easy to repair.

[0071] Comparative Example 2

[0072] A method for preparing a titanium-based enamel coating is basically the same as that of Example 2, except that the aluminum silicate fiber is omitted from the grinding additive in step (3).

[0073] The titanium-based enamel coating was heated to 700°C and kept warm for 20 minutes, then placed in cold water at 20°C for hot and cold shock. After seven cycles of hot and cold shock tests, cracks appeared on the surface, and local peeling occurred as point-like peeling.

[0074] By comparing Comparative Example 2 with Example 2, it can be found that the thermal shock resistance of the titanium-based enamel coating prepared in Comparative Example 2 is significantly deteriorated. This is due to the lack of the participation of aluminum silicate fibers. Not only can the crack propagation be effectively inhibited, but the direct contact area between the enamel and the titanium powder is also increased, increasing the risk of interfacial reaction between the two, thereby reducing the internal interface bonding strength of the coating.

[0075] Comparative Example 3

[0076] A method for preparing a titanium-based enamel coating is basically the same as that of Example 2, except that titanium powder is omitted from the grinding material in step (3).

[0077] The titanium-based enamel coating was heated to 700°C and kept warm for 20 minutes, then placed in 20°C cold water for hot and cold shock. After 10 cycles of hot and cold shock tests, three pinholes visible to the naked eye appeared on the surface.

[0078] By comparing Comparative Example 3 with Example 2, it can be found that the thermal shock resistance of the titanium-based enamel coating prepared in Comparative Example 3 is significantly deteriorated. This is because the lack of titanium powder causes the additional energy to be unable to be effectively absorbed during the thermal shock process, and the generated microcracks cannot be repaired.

[0079] Example 3

[0080] A method for preparing a titanium-based enamel coating that is resistant to thermal shock and suitable for low-temperature firing, the specific steps are as follows:

[0081] (1) In terms of mass percentage, the batch material for preparing enamel frit is as follows: SiO2 56%, B2O3 14%, Na2O 9%, Li2O 3%, BaO 2%, SrO 2%, ZnO5%, ZrO2 2%, CoO 3%, NiO 1%, CuO 1%, MoO31%, Sb2O3 1%;

[0082] (2) Melting the batch materials of the enamel frit at 1550°C for 100 minutes to obtain an enamel melt, drawing the enamel melt with a metal rod, and after testing that there are no nodules within 1 m of the drawn wire, pouring the enamel melt into water for water quenching, and drying at 150°C to obtain an enamel frit;

[0083] (3) After mixing the enamel frit and the grinding additive, the mixture is ball-milled and sieved through a 60-mesh sieve to obtain an enamel glaze slurry;

[0084] The grinding additives are titanium powder, aluminum silicate fiber, sodium nitrite, clay and water; based on the amount of enamel frit, the mass percentages of the components in the grinding additives are: titanium powder 1%, aluminum silicate fiber 2%, sodium nitrite 0.15%, clay 6%, water 35%;

[0085] (4) Pretreatment of the titanium substrate: grinding the surface of the titanium substrate with 40-mesh sandpaper, then ultrasonically cleaning the titanium substrate with anhydrous ethanol and deionized water for 30 min respectively, and then drying the titanium substrate;

[0086] (5) Wet-spraying the enamel slurry on the pretreated titanium substrate surface, and then placing the titanium substrate sprayed with the enamel slurry in an oven at 100°C for 30 minutes to dry, and then sintering in a box-type resistance furnace at 840°C for 10 minutes to obtain a titanium-based enamel coating that is resistant to cold and heat shock and suitable for low-temperature sintering;

[0087] Among them, the spraying pressure is 2 atmospheres.

[0088] The final titanium-based enamel coating that is resistant to cold and heat shocks and suitable for low-temperature firing has a thickness of 85μm; the titanium-based enamel coating that is resistant to cold and heat shocks and suitable for low-temperature firing is heated to 700℃ and kept warm for 20 minutes, and then placed in 20℃ cold water for cold and heat shock. After 23 cycles of cold and heat shock tests, no cracks or peeling visible to the naked eye appeared.

[0089] Comparative Example 4

[0090] A method for preparing a titanium-based enamel coating is basically the same as that of Example 3, except that titanium powder and aluminum silicate fiber are omitted from the grinding additives in step (3).

[0091] The titanium-based enamel coating was heated to 700°C and kept warm for 20 minutes, then placed in 20°C cold water for hot and cold shock. After 15 cycles of hot and cold shock tests, three pinholes visible to the naked eye appeared on the surface.

[0092] By comparing Comparative Example 4 with Example 3, it can be found that the thermal shock resistance of the titanium-based enamel coating prepared in Comparative Example 4 is significantly deteriorated. This is because the crack propagation inside the enamel can neither be effectively suppressed nor repaired.

[0093] Comparative Example 5

[0094] A method for preparing a titanium-based enamel coating is basically the same as that of Example 3, except that the aluminum silicate fiber is omitted from the grinding additive in step (3).

[0095] The titanium-based enamel coating was heated to 700°C and kept warm for 20 minutes, then placed in 20°C cold water for hot and cold shock. After 10 cycles of hot and cold shock tests, a point-like peeling appeared on the surface.

[0096] By comparing Comparative Example 5 with Example 3, it can be found that the thermal shock resistance of the titanium-based enamel coating prepared in Comparative Example 5 is significantly deteriorated. Although titanium powder helps to promote the healing of cracks, the interface products generated by its reaction with enamel will weaken the internal bonding strength of the enamel. Therefore, the thermal shock resistance of the titanium-based enamel coating in Comparative Example 5 is poor.

[0097] Comparative Example 6

[0098] A method for preparing a titanium-based enamel coating is basically the same as that of Example 3, except that titanium powder is omitted from the grinding material in step (3).

[0099] The titanium-based enamel coating was heated to 700°C and kept warm for 20 minutes, then placed in 20°C cold water for hot and cold shock. After 21 cycles of hot and cold shock tests, two point-like peelings appeared on the surface.

[0100] By comparing Comparative Example 6 with Example 3, it can be found that the thermal shock resistance of the titanium-based enamel coating prepared in Comparative Example 6 deteriorates. This is because the aluminum silicate fiber can only inhibit crack propagation but cannot repair the crack.

[0101] Compared with Comparative Examples 1-3, Comparative Examples 4-6 introduce more transition metal oxides, which can inhibit the porous Ti x Si y The formation of interface products enhances the bonding strength between the enamel and the titanium substrate. The increase in interface bonding strength is beneficial to improving the thermal shock resistance of the enamel.

[0102] Example 4

[0103] A method for preparing a titanium-based enamel coating that is resistant to thermal shock and suitable for low-temperature firing, the specific steps are as follows:

[0104] (1) In terms of mass percentage, the batch material for preparing enamel frit is as follows: SiO2 56%, B2O3 14%, Na2O 9%, Li2O 3%, BaO 2%, SrO 2%, ZnO5%, ZrO2 2%, CoO 3%, NiO 1%, CuO 1%, MoO31%, Sb2O3 1%;

[0105] (2) Melting the batch materials of the enamel frit at 1550°C for 100 minutes to obtain an enamel melt, drawing the enamel melt with a metal rod, and after testing that there are no nodules within 1 m of the drawn wire, pouring the enamel melt into water for water quenching, and drying at 150°C to obtain an enamel frit;

[0106] (3) After mixing the enamel frit and the grinding additive, the mixture is ball-milled and sieved through a 60-mesh sieve to obtain an enamel glaze slurry;

[0107] The grinding additives are titanium powder, aluminum silicate fiber, sodium nitrite, clay and water. Based on the amount of enamel frit, the mass percentages of the components in the grinding additives are: titanium powder 0.25%, aluminum silicate fiber 3%, sodium nitrite 0.15%, clay 6%, water 35%.

[0108] (4) Pretreatment of the titanium substrate: grinding the surface of the titanium substrate with 40-mesh sandpaper, then ultrasonically cleaning the titanium substrate with anhydrous ethanol and deionized water for 30 min respectively, and then drying the titanium substrate;

[0109] (5) Wet-spraying the enamel slurry on the pretreated titanium substrate surface, and then placing the titanium substrate sprayed with the enamel slurry in an oven at 100°C for 30 minutes to dry, and then sintering in a box-type resistance furnace at 840°C for 10 minutes to obtain a titanium-based enamel coating that is resistant to cold and heat shock and suitable for low-temperature sintering;

[0110] Among them, the spraying pressure is 2 atmospheres.

[0111] The final titanium-based enamel coating that is resistant to cold and heat shocks and suitable for low-temperature firing has a thickness of 118μm; the titanium-based enamel coating that is resistant to cold and heat shocks and suitable for low-temperature firing is heated to 700℃ and kept warm for 20 minutes, and then placed in 20℃ cold water for cold and heat shock. After 26 cycles of cold and heat shock tests, no cracks or peeling visible to the naked eye appeared.

Claims

1. A titanium-based enamel coating that is resistant to thermal shock and suitable for low-temperature firing, characterized in that: The invention comprises enamel frit and grinding additives, wherein the grinding additives include titanium powder, aluminum silicate fiber, sodium nitrite, clay and water; The formula of the enamel frit is as follows, by mass percentage: SiO2 and B2O3 69-70%, Na2O and Li2O 12-14.5%, two of CaO, BaO and SrO 1-4%, ZnO 1-5%, ZrO2 2-6.5%, TiO2 0-3%, and the balance of two or more of CoO, NiO, CuO, MnO2, MoO3 and Sb2O3; Based on the amount of enamel frit, the mass percentages of the components in the grinding additives are: titanium powder 0.25-2%, aluminum silicate fiber 2-3%, sodium nitrite 0.13-0.17%, clay 5-7%, water 33-36%; The low temperature sintering temperature is 835~845℃.

2. The titanium-based enamel coating resistant to thermal shock and suitable for low-temperature firing according to claim 1, characterized in that: The thickness of the titanium-based enamel coating, which is resistant to thermal shock and suitable for low-temperature firing, is 85~115μm.

3. The titanium-based enamel coating resistant to thermal shock and suitable for low-temperature firing according to claim 1, characterized in that: The titanium-based enamel coating, which is resistant to thermal shock and suitable for low-temperature firing, was heated to 700°C and kept warm for 20 minutes. It was then placed in 20°C cold water for thermal shock. After 22 to 26 cycles of thermal shock tests, no cracks or peeling visible to the naked eye appeared.

4. The method for preparing a titanium-based enamel coating that is resistant to thermal shock and suitable for low-temperature sintering according to any one of claims 1 to 3, characterized in that: First, an enamel frit is prepared, and then the enamel frit is mixed with an abrasive to obtain an enamel slurry. Subsequently, the titanium substrate is pretreated to remove surface dirt, and then the enamel slurry is wet-sprayed on the surface of the pretreated titanium substrate. Finally, the titanium substrate sprayed with the enamel slurry is dried and fired at 835-845°C to obtain a titanium-based enamel coating that is resistant to cold and heat shocks and suitable for low-temperature firing.

5. The method for preparing a titanium-based enamel coating that is resistant to thermal shock and suitable for low-temperature firing according to claim 4, characterized in that: The specific preparation steps are as follows: (1) Prepare the batch materials of enamel frit according to the formula: (2) melting the batch materials of the enamel frit to obtain an enamel melt, then quenching the enamel melt with water, and drying to obtain the enamel frit; (3) After mixing the enamel frit and the grinding additive, the enamel slurry is obtained by ball milling and sieving; (4) Pretreatment of the titanium substrate: polishing the surface of the titanium substrate, then ultrasonically cleaning the titanium substrate with anhydrous ethanol and deionized water respectively, and then drying the titanium substrate; (5) The enamel slurry is wet-sprayed on the surface of the pretreated titanium substrate, and then the titanium substrate sprayed with the enamel slurry is placed in an oven to dry, and then placed in a box-type resistance furnace for firing, to obtain a titanium-based enamel coating that is resistant to cold and heat shock and suitable for low-temperature firing.

6. The method for preparing a titanium-based enamel coating that is resistant to thermal shock and suitable for low-temperature firing according to claim 5, characterized in that: In step (2), the batch materials of the enamel frit are melted at 1540-1570° C. for 100-120 min to obtain an enamel melt.

7. The method for preparing a titanium-based enamel coating that is resistant to thermal shock and suitable for low-temperature firing according to claim 5, characterized in that: The mesh size of the sieve used in step (3) is 60 mesh.

8. The method for preparing a titanium-based enamel coating that is resistant to thermal shock and suitable for low-temperature firing according to claim 5, characterized in that: In step (4), the surface of the titanium substrate is polished using sandpaper with a mesh size of 40 to 60.

9. The method for preparing a titanium-based enamel coating that is resistant to thermal shock and suitable for low-temperature firing according to claim 5, characterized in that: In step (5), the drying temperature is 95-105°C and the drying time is 25-35 minutes.

10. The method for preparing a titanium-based enamel coating that is resistant to thermal shock and suitable for low-temperature firing according to claim 5, characterized in that: The firing time in step (5) is 9 to 11 minutes.

Citation Information

Patent Citations

  • Hydrogen or hydrogen isotope infiltration resisting vitreous vallation layer for titanium or titanium alloy and preparation method thereof

    CN101215710A

  • Enamel coating for titanium alloy and preparation method thereof

    CN107601882A

  • Porcelain enamel with superior adherence and acid resistance simultaneously and preparation method thereof

    CN101570397A

  • Heat-insulating coating material for firing enamel on surface of titanium alloy and preparation method thereof

    CN104193173A